Essays on corporate finance - XUE SHUYU, Shuyu (Institutional Knowledge at Singapore Management University, 2020)
This dissertation has two essays on corporate finance. In the first chapter, I investigate the dual-class structure. The dual-class structure is often regarded as poor corporate governance and the source of agency problems. However, I find that, for companies with high information asymmetry and long investment horizon, dual-class structure delivers higher operating performance and valuation ratios. These performing dual-class companies tend to have a higher investment in intangibles, more innovations, less pay-out, and less CEO compensation. The findings suggest that dual-class structure could be optimal in empowering information-advantageous inside shareholders and ensuring corporate long-term goals. In the second chapter of my dissertation, we study how air pollution influences firm performance. Air pollution is a growing hazard to human health. This study examines whether air pollution affects the formation of corporate human capital and thereby performance. We find that people exhibit an intention to look for jobs in less polluted areas on days when air pollution occurs in the area where they are located, suggesting that an individual’s sort in response to air pollution. Consistent with this sorting prediction, we find that the level of firms’ skilled executives and employees significantly drops when pollution information becomes real-time accessible and when the pollution level increases in their locations, especially in places where concerns for health is more sensitive to air pollution. Moreover, parallel reductions in firm productivity and value are found and become more salient when firms have a greater dependence on human capital.